Maintenance of Immune Homeostasis through ILC/T Cell Interactions - von Burg, Nicole; Turchinovich, Gleb; Finke, Daniela (Frontiers in Immunology, 2015)
Innate lymphoid cells (ILCs) have emerged as a new family of immune cells with crucial functions in innate and adaptive immunity. ILC subsets mirror the cytokine and transcriptional profile of CD4+ T helper (TH) cell subsets. Hence, group 1 (ILC1), group 2 (ILC2) and group 3 (ILC3) ILCs can be distinguished by the production of TH1, TH2, and TH17-type cytokines, respectively. Cytokine release by ILCs not only shapes early innate immunity, but can also orchestrate TH immune responses to microbial or allergen exposure. Recent studies have identified an unexpected effector function of ILCs as antigen presenting cells (APCs). Both ILC2s and ILC3s are able to process and present foreign antigens (Ags) via major histocompatibility complex (MHC) class II, and to induce cognate CD4+ T cell responses. In addition, Ag-stimulated T cells promote ILC activation and effector functions indicating a reciprocal interaction between the adaptive and innate immune system. A fundamental puzzle in ILC function is how ILC/T cell interactions promote host protection and prevent autoimmune diseases. Furthermore, the way in which microenvironmental and inflammatory signals determine the outcome of ILC/T cell immune responses in various tissues is not yet understood. This review focuses on recent advances in understanding the mechanisms that coordinate the collaboration between ILCs and T cells under homeostatic and inflammatory conditions. We also discuss the potential roles of T cells and other immune cells to regulate ILC functions and to maintain homeostasis in mucosal tissues.